Developing French for Specific Purposes to Enhance Foreign Language Skills of Curriculum and Teaching Students in The University of Calabar - Kalu, Goodness Uka; Umukoro, Gloria Mayen (Fakultas Sastra - Universitas Muslim Indonesia, 2024)
Traditional language teaching methodologies often fall short in meeting the specialized needs of learners who require language skills for specific professional contexts. This gap has led to the emergence of French for Specific Purposes (FSP), a subfield focused on equipping learners with the necessary skills to function effectively in their chosen professions. This study aimed to evaluate the effectiveness of FSP in enhancing language skills and cultural knowledge among learners in the Department of Curriculum and Teaching, Faculty of Educational Foundation Studies. To achieve this objective, three research questions were formulated. A literature review was conducted based on the study variables, and a descriptive research design was employed. The target population comprised all students and instructors in the Department of Curriculum and Teaching, University of Calabar, who are involved in French language courses. A purposive sample of 31 respondents, including 25 learners and 6 instructors, was selected. Data were collected through semi-structured questionnaires and interviews, providing rich qualitative insights. Thematic analysis techniques, involving simple percentages, were used to analyze the qualitative data. The results revealed that learners in the Department of Curriculum and Teaching face specific language needs and challenges. Additionally, FSP instruction was found to significantly enhance learners' language proficiency and cultural understanding. The study also indicated that FSP instruction positively influences the perceptions and attitudes of both learners and instructors towards FSP. The findings of this study have important implications for the design and implementation of FSP courses, especially in the context of tertiary education. These insights are valuable for curriculum developers, educators, and policymakers aiming to improve language education and ensure its alignment with professional and academic needs.